How to produce gladiolus corms? - Tomiozzo, Regina; Uhlmann, Lilian Osmari; Becker, Camila Coelho; Schwab, Natalia Teixeira; Streck, Nereu Augusto; Balest, Darlan Scapini (Ornamental Horticulture, 2019)
Gladiolus (Gladiolus x grandiflorus Hort.), also called as Palma-de-Santa-Rita, is culturally known in Brazil as the All Soul's’ Day flower. In recent years, it has also become popular in other special dates due to its robustness, liveliness, and magnificence. However, there are challenges regarding the cut flower production, since the largest producer investment is the corm acquisition. Due to the insufficiency of technical information, there are no fully established corm production protocols for gladiolus. Therefore, this technical article has the objective of bringing information related to the gladiolus corms production technique, in view of the sustainability of the production.